Lymph Node Enlargment - Malignant or Benign - Khan, Jahanzeb; Khan, Gulalai Wali (Journal of Postgraduate Medical Institute, 2011)
Normal lymphnodes are impalpable except, in some very thin individuals palpable enlargement is referred to as the nodes picked upt by the physician clinically, detection by radiography was not involved. It apples mainly to adolescence and adults, a different array of diseases underlies enlarged lymphnodes in infants and children. It does not include therapy and children. it does not include therapy and the diagnostic evaluation of rare disease.